Study on the fault Petri nets of the unmanned roadheader based on the transition memory - Yang Jianjian; Tang Zhiwei; Liu Qiang; Wang Fengdong; Yin Tongzhou; Wu Miao (矿业科学学报, 2017)
Unmanned roadheader is the realization of the concept of unmanned mining technology, coal mine intelligent mining requires roadheader with intelligent diagnosis technology. Based on the analysis of the traditional Petri nets application in the field of fault diagnosis, this paper gives fault diagnosis modeling expression of different classification problem & a kind of theory, and the abstraction of three big problems of science and technology in the field of fault diagnosis. Here, we introduce transition token matrix representation of transition memory in order to express path of fault propagation. On this basis, from several aspects which are the new fault Petri nets definition, correlation matrix improvement, equation of state, transition memory, this paper discusses the theory and technology of fault definition of roadheader Petri nets based on transition memory. Finally, it is proved that the expression form of intelligent diagnosis function and the consistent expression of intelligent reasoning of fault propagation path.